Między realizmem a pragmatyzmem: Polska polityka zagraniczna w ujęciu Stanisława Cata-Mackiewicza na łamach wileńskiego „Słowa” w latach 30. XX wieku - Rafałowski, Hubert (PRAWO i WIĘŹ, 2025)
The article discusses Stanisław Cat-Mackiewicz's views on Polish foreign policy in the 1930s, presented in the Vilnius daily “Słowo”. The publicist consistently criticized the illusions accompanying the foreign policy of the Second Polish Republic, particularly the excessive trust placed in France and Great Britain, which—in his opinion—were not prepared to offer real support to Poland in the event of a war with Germany. He supported the signing of the non-aggression pact with the Third Reich in 1934, considering it a step toward greater independence of Polish diplomacy. Stanisław Mackiewicz advocated a policy of balance between Germany and the Soviet Union, while firmly warning against the threat posed by Bolshevism. Although he did not call for breaking off diplomatic relations with the USSR, he demanded a firm and clearly anti-communist stance from the Polish state. In the article, Mackiewicz appears as a political thinker guided by realism in international affairs, in opposition to the strategy pursued by Minister Józef Beck.